Soil water characteristic curves for laterite soil at different water contents and methods as lining system. (May 2019) - Bello Yamusa, Yamusa; Azril Hezmi, Muhammad; Ahmad, Kamarudin; Anuar Kassim, Khairul; Sa'ari, Radzuan; Alias, Noraliani; Mustaffar, Mushairry; Kassim, Azman; Safuan A. Rashid, Ahmad
Abstract: Preventing groundwater contamination from the most common method of solid waste disposal technique i.e. landfilling is by proving hydraulic barriers. Accordingly, water movement in unsaturated soil is important in the analysis of leachate migration in soil material used as hydraulic barrier in waste containment systems. A full-scale experiment would be prohibitively costly and time consuming. The only feasible recourse therefore is to construct a model, which reasonably portray the behaviour of the full-scale system and simulate the relevant physical parameters and describes the overall significant characteristics of the transport phenomena. This paper presents the trends and patterns of soil water characteristic curves (SWCC) in terms of volumetric water content versus soil suction developed for compacted laterite soil specimens using data from pressure plate tests. Specimens were prepared at three different water contents corresponding to dry of optimum, optimum, and wet of optimum conditions. Models suggested by Brooks and Corey (BC), van Genuchten (VG), and Fredlund and Xing (FX) were used to obtain curve fitting parameters using the program "SWRC Fit" which performed nonlinear fitting of soil water retention curves. The SWRC Fit can simultaneously calculate the fitting parameters of these models with Root Mean Square Error values and draw the fitting curves. By comparing the results of the models using SWRC Fit, the model that best fits the laterite soil investigated will be chosen to be used for further analysis. The results show that the BC model represents the soil water retention curves better than the VG and FX models when the soil has distinct air entry suction. On the other hand, the VG and FX models can fit most soil water retention curves very well when discussion on the pore-size distribution is desired.